Vulnerability of Patagonian planktonic copepods to fluctuations in temperature and UVR - Dieguez, Maria del Carmen (2014)
The aim of this investigation is to address the impact of fluctuations in temperature and ultraviolet radiation (UVR) on three species of South American copepods, Boeckella antiqua, B. gracilis and B. brevicaudata. These copepods are cold stenotherm and occur in high latitude lakes of South America and in mountain lakes in the Andes. The forecast scenarios for climate change in southern South America anticipate raising temperature and UVR levels. These changes may have the potential to impact high altitude and latitude ecosystems, including lakes and their cold adapted biota, such as those in Patagonia. Laboratory experiments, consisting of 10 day and 2 day incubations, were set up to analyse copepod mortality in relation with: (i) temperature, and (ii) the combined effect of temperature (5, 8, 12, 16, 20°C) and UV-B dose (61, 194 and 324 J m−2). The results obtained showed up that temperature is a limiting factor for B. brevicaudata that did not survive above 12°C. B. antiqua and B. gracilis withstood the temperature range although their mortality was higher at 12-16°C. The survivorship of these copepod species to radiation was found to depend on the UV-B dose, resulting in higher mortality at the highest UV-B dose. Overall, at least one Boeckella species showed an acute sensitivity to increasing temperature, and the three species studied proved tolerant to the UV-B experimental exposure. The survivorship patterns observed in Boeckella species reflect clearly their adaptation to high solar radiation exposure and to temperate to cold environmental conditions.